What a Difference Immigration Law Makes: PISA results, migration background, socioeconomic status and social mobility in Europe and traditional countries of immigration - Horst Entorf; Nicoleta Minoiu (Technische Universität Darmstadt, Department of Law and Economics, 2004)
The purpose of this article is to evaluate the importance of social class, migration background and command of national languages for the PISA school performance of teenagers living in European countries (France, Finland, Germany, United Kingdom, and Sweden) and traditional countries of immigration (Australia, Canada, New Zealand and the US). Econometric results show that the influence of the socioeconomic background of parents differs strongly across nations, with the highest impact found for Germany, the UK and US, whereas social mobility appears to be more likely in Scandinavian countries and in Canada. Further empirical results show that for students with a migration background a key for catching up is the language spoken at home. We conclude that educational policy should focus on integration of immigrant children in schools and preschools, with particular emphasis on language skills at the early stage of childhood.
Keywords: 330; Einwanderungsrecht; Bildungsniveau; Familiensoziologie; Soziale Schicht; Soziale Mobilität; Schätzung; OECD-Staaten; Migranten